Use of an enzyme-linked immunosorbent assay that utilizes the Tc13Tul antigen of Trypanosoma cruzi to monitor patients after treatment with benznidazole - Santamaría, Ana Lorena (2013)
Fil: Santamaría, Ana Lorena. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.